Impact of capital structure on stock prices of listed beverage, food and tobacco companies in Sri Lanka: A panel data approach - Ravindran, M.; Thavarasasingam, H.; Anandasayanan, S. (Rajarata University of Sri Lanka, 2018)
The share price of a firm is affected by various factors. Determination of share price is not an easy task. The decision of capital structure is critical for any organization in any given sector or economy. It is usually challenging for business firms to figure out the right mixture of equity and debt. The decision is significant because of the requirement to maximize returns to various organizational departments. Share prices are one of the major avenues of investment which gives higher returns to investors. Several studies have proven that share price of firms are explained by its capital structure. From the survey it is known that capital structure of a firm significantly impacts its stock price, but the results are not consistent and it varies from industry to industry and economy to economy. The main objective of the study is to study the impact of the capital structure on stock prices of listed beverage, food and tobacco companies in Sri Lanka. A survey was carried out on all the companies during the period 2011 to 2017. In this study debt to equity ratio and debt to total asset ratio were considered as the independent variables and annual ending market price of share was considered as the dependent variable. Hypotheses were tested by employing panel least square method approach. The findings revealed that the influence of capital structure on share price was statistically significant. Decisions regarding capital structure should be taken with an eye on its negative impact on firm value.
Keywords: Capital structure; Debt and equity; Share price